Dakwah Islam bagi Gen-Z: Peluang, Tantangan, dan Strategi: Islamic Preaching for Gen-Z: Opportunities, Challenges, and Strategies - Azwar, Azwar; Iskandar, Iskandar (DIRASAH: Jurnal Kajian Islam, 2024)
This study aims to identify various opportunities and challenges in conveying Islamic preaching (dakwah) to Gen-Z, as well as formulate effective and relevant dakwah strategies for this demographic. The research employs a qualitative method with a descriptive-analytical approach. The findings indicate that technology and social media offer significant opportunities for dakwah due to their wide accessibility and creative tools for message delivery. Additionally, their curiosity and openness to in-depth learning about global issues present opportunities for comprehensive religious education. However, there are significant challenges, such as distractions from non-religious content, the influence of secularism and materialism, and cultural and value diversity. Effective dakwah strategies include utilizing technology and social media to create creative and engaging content, as well as digital platforms for dakwah dissemination. Consequently, preachers and Islamic organizations need to adapt their dakwah methods to effectively leverage technology and social media, such as producing content that aligns with Gen-Z’s preferences and using platforms they frequent.